PERANAN KONSORSIUM BAKTERI ENDOFIT PADA KARAKTER PERAKARAN DAN HASIL PADI PADA BERBAGAI DOSIS NITROGEN DAN PHOSPHOR DI LAHAN SUBOPTIMAL TADAH HUJAN - Aziez, Achmad Fatchul; Budiyono, Agus; Wiyono, Wiyono; Sari, Sri Mardhika; Ramdani, Aziz; Paiman, Paiman; Purwaningsih, Okti (Jurnal Ilmiah Hijau Cendekia, 2024)
Rice (Oryza sativa L.) is a vital food crop in Indonesia's economy. It is grown in both irrigated and rainfed rice fields. However, rainfed rice fields have low nutrient content, requiring significant fertilization. To reduce reliance on chemical fertilizers, agricultural technological advancements are necessary, including the use of endophytic bacteria. The research aimed to assess the impact of an endophytic bacterial consortium on rice rooting and yield under various nitrogen and phosphorus doses in suboptimal rainfed land. The study was conducted in Demangan Village, Sambi District, Boyolali Regency, from March 2023 to June 2023, using a factorial Complete Group Design. The research consisted of two factors , each repeated three times. The first factor was nitrogen fertilizer, with four levels: no urea, 100 kg/ha urea, 200 kg/ha urea, and 300 kg/ha urea. The second factor iwas phosphorus fertilizer, with four levels,: no phosphorus, 80 kg/ha phosphorus, 160 kg/ha phosphorus, and 240 kg/ha phosphorus. The observed parameters included fresh root weight, dry root weight, root volume, root length, root diameter, root surface area, weight of 1000 grains, grain weight per plant, and grain weight per plot. The results revealed no significant effects of nitrogen, doses, phosphorus doses, or interactions between nitrogen and phosphorus doses on any of the observed parameters. In conclusion, the application of an endophytic bacterial consortium can reduce the need for nitrogen and phosphorus fertilizers in rainfed rice fields.